A Bibliometric Study on the Implementation of Halal Practices in West Sumatera with VOSviewer - Arham, Qumil Laila; Yasri , Yasri; Abror, Abror (Universitas Muhammadiyah Pontianak, 2026)
This study aims to identify and analyse key references on halal implementation in West Sumatra through a bibliometric analysis using VOSviewer and citation data from Google Scholar. A systematic review yielded 21 significant references published between 2018 and 2025. The highest publication activity occurred in 2020, with Surya Elfitra Desy emerging as the most prolific author. This study maps journal and author contributions, highlighting trends and gaps in the field. The findings provide a foundation for future research on halal practices in various sectors and contribute to the academic discourse on halal implementation in the region.